Science and technology in Portuguese newspapers, 1854-1918 - Almeida, Maria Antónia (Academia Letters, 2021)
These are results of a research on the popularization of science and technology. The goal was to find out how scientific knowledge reached the people, using newspapers as source of information. A database was built with over 6.700 news and advertisements from 1854 to 1918. These are a few of the main concerns of the press at the time.